Governance-related conditionalities of the international financial institutions - kapur, Devesh (UN New YorkUS, 2000)
Examines the new found enthusiasm for governance-related conditionalities in the International Monetary Fund (IMF) and World Bank lending. Notes that this new agenda has focused in particular on legislative and institution-building efforts by borrowers to increase accountability, transparency, the rule of law, and participation. Attempts to document this trend by analysing a sample of 25 upper-tranche arrangements in 1999. Highlights critical weaknesses in the new agenda. Examines a brief account of some alternatives to conditionality, as currently practised. Raises some troubling implications of this new agenda for the international financial institutions (IFIs) themselves, especially with regard to their operational effectiveness, their legitimacy and their fairness.